FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERASAAN KELELAHAN KERJA PERAWAT RUANG RAWAT INAP [FACTORS RELATED TO INPATIENT NURSES' WORK FATIGUE] - Rachelka Nugraheni; Desi Ramita Winda; Ineke Patrisia; Christie Lidya Rumerung (Universitas Pelita Harapan, 2023)
Nurses are medical personnel who provide nursing care to patients. Nurses need extra energy in doing work, so they are prone to fatigue. The data of unstructured interviews revealed that eight out of ten nurses experienced work fatigue.These nurses found it to be easily anxious, angry, and difficult to concentrate. The purpose of this study was to determine the relationship between age, gender, years of service, work shifts, nutritional status, and health conditions with feelings of work fatigue in inpatient nurses. The study used a descriptive quantitative method with a population of 70 inpatient nurses. Total sampling technique was utilized, resulting in 70 respondents. The research has indeed considered and passed the research ethics. The study used a standardized questionnaire to measure the feelings of work fatigue. Based on the chi-square statistical test, it was found that there was no relationship between gender, length of work, work shifts and health conditions with feelings of work fatigue, where the p-value of each factor was > 0.05. While the statistical test for age and nutritional status factors using the Spearman Rank correlation test showed that there was no relationship between age and feelings of work fatigue, with a value of significance 0.682 > 0.05. Furthermore, there was a relationship between nutritional status and feelings of work fatigue, with a value of significance 0.025 < 0.05. Qualitative research needs to be carried out further to be able to see in more detail the factors that influence feelings of burnout. BAHASA INDONESIA ABSTRAK Perawat merupakan tenaga medis yang memberikan asuhan keperawatan kepada pasien. Perawat membutuhkan tenaga ekstra dan maksimal dalam melakukan pekerjaan, sehingga rentan menimbulkan kelelahan. Hasil wawancara tidak terstruktur diperoleh data yaitu delapan dari sepuluh perawat mengalami kelelahan kerja, perawat-perawat tersebut merasa sulit berkonsentrasi, mudah cemas, dan mudah marah. Tujuan penelitian ini ingin mengetahui hubungan antara faktor usia, jenis kelamin, masa kerja, shiftkerja, status gizi dan kondisi kesehatan dengan perasaan kelelahan kerja perawat rawat inap. Penelitian menggunakan metode kuantitatif deskriptif dengan populasi 70 responden perawat rawat inap, menggunakan teknik sampling total sampling sehingga responden sebanyak 70 responden. Penelitian memperhatikan etik-etik penelitian dan telah lolos etik . Penelitian menggunakan kuesioner baku alat ukur perasaan kelelahan kerja. Berdasarkan uji statistik chisquare didapatkan tidak terdapat hubungan antara jenis kelamin, masa kerja, shiftkerja dan kondisi kesehatan dengan perasaan kelelahan kerja, dimana nilai p-valuemasing-masing faktor > 0,05. Sedangkan uji statistik untuk faktor usia dan status gizi menggunakan uji korelasi RankSpearman diperoleh hasil tidak terdapat hubungan antara umur dengan perasaan kelelahan kerja diperoleh nilai signifikansi 0,682 > 0,05 dan adanya hubungan status gizi dengan perasaan kelelahan kerja diperoleh nilai signifikansi 0,025 < 0,05. Penelitian kualitatif perlu dilakukan lebih lanjut untuk bisa melihat lebih detail faktor yang memengaruhi perasaan kelelahan kerja.